A educação infantil no contexto da creche: um estudo sobre a educação, o cuidado da criança de zero a três anos e a formação de professores no município de Marília,SP - Spada, Ana Corina Machado [UNESP] (2006)
This research discusses the children.s education developed in public child day care centers. Historically, the attendance developed by child day care had been directed to children from popular class in Brazil and specially in Brazil, this kind of attendance were developed based on philanthropic work, with practices inside the institutions purely based on physical care. Considering on these elements that influenced the practices used inside the child day care space, as well the public policies created to this modality of education, this research intended to identify how has the children.s education at public child day care has been developed. To attend this intention, the research objectives concentrated on verify the conceptions about Children.s Education and about infancy between: principals, teacher.s and Children.s Education auxiliaries that work with children from zero to three years old; investigate the practices that composes the daily routine of children.s education developed by children between zero to three years, verifying how it is organized in time and space; investigate if and how the attendance in children.s education at Marília is organized according to Official Public Policies of Children.s Education; discuss the importance of these investigations from teacher.s formation. The research were developed with two public child day care at Marília, SP, Brazil and the methodology used consisted on a qualitative approach, in a ethnographic modality (BOGDAN; BIKLEN, 1994). The search reveals that the daily routine in both institutions researched emphasizes the physical care instead of the education, it means, the aspects concerning hygiene and alimentation receive more attention then the elements that are related effectively with the education.